Two advanced-aged patients with diabetic striatopathy: a case report and literature review - Liu, Yikai; Huang, Wentan; Mo, Zewei; Wei, Weiping (Frontiers in Endocrinology, 2026)
BackgroundDiabetic striatopathy (DS) is a rare neurological complication of diabetes mellitus, characterized by acute choreiform or ballistic movements and hyperintense basal ganglia lesions on T1-weighted MRI. While non-ketotic hyperglycemia is commonly implicated, DS can also occur in ketotic states.Case presentationWe report two elderly patients with long-standing, poorly controlled diabetes. Case 1, an 80-year-old male, presented with bilateral lower limb choreiform movements and delirium. Case 2, a 92-year-old female, developed right-sided hemichorea after discontinuing hypoglycemic therapy. Both patients had hyperglycemia with ketosis and characteristic basal ganglia T1 hyperintensity. Intensive glycemic control and symptomatic therapy led to complete resolution of involuntary movements in both cases.ConclusionThese cases highlight the heterogeneous clinical presentations of DS in advanced-aged patients and emphasize the importance of early recognition and prompt metabolic correction to achieve favorable neurological outcomes.